Young Perspectives for Old Diseases: Recent Updates on the Understanding and Therapies for Neurodegenerative Diseases (Bentham Science Publishers, 2023)
Young Perspectives for Old Diseases is a collaborative monograph describing the current understanding of common neurodegenerative diseases. The monograph focuses on the molecular and cellular mechanisms responsible for neurodegeneration and the scientific advances that have paved the way for potential therapeutic options for patients. Reviews presented in this book present carefully validated research findings. The book begins with a section devoted to general mechanisms of neuronal death and explains the challenges of translating the scientific discoveries to the clinic. In section two, there are reviews on specific cellular dysfunctions that are common to more than one form of neurodegenerative disease, exploring the universal pathophysiology responsible for degenerating neurones. Findings on common neurodegenerative diseases are also reviewed in further detail followed by information on advances in therapeutic techniques that could be translated to a clinical setting. This book is intended as a primer as well as an update for molecular biologists and medical researchers on the mechanism of neurodegeneration and progress in the treatment of associated diseases.